Screening of Saccharomyces cerevisiae metabolite transporters by 13C isotope substrate labeling - Stanchev, Lyubomir Dimitrov; Møller-Hansen, Iben; Lojko, Pawel; Rocha, Catarina; Borodina, Irina (Frontiers in Microbiology, 2023)
The transportome of Saccharomyces cerevisiae comprises approximately 340 membrane-bound proteins, of which very few are well-characterized. Elucidating transporter proteins' function is essential not only for understanding central cellular processes in metabolite exchange with the external milieu but also for optimizing the production of value-added compounds in microbial cell factories. Here, we describe the application of 13 C-labeled stable isotopes and detection by targeted LC-MS/MS as a screening tool for identifying Saccharomyces cerevisiae metabolite transporters. We compare the transport assay's sensitivity, reproducibility, and accuracy in yeast transporter mutant cell lines and Xenopus oocytes. As proof of principle, we analyzed the transport profiles of five yeast amino acid transporters. We first cultured yeast transporter deletion or overexpression mutants on uniformly labeled 13 C-glucose and then screened their ability to facilitate the uptake or export of an unlabeled pool of amino acids. Individual transporters were further studied by heterologous expression in Xenopus oocytes, followed by an uptake assay with 13 C labeled yeast extract. Uptake assays in Xenopus oocytes showed higher reproducibility and accuracy. Although having lower accuracy, the results from S. cerevisiae indicated the system's potential for initial high-throughput screening for native metabolite transporters. We partially confirmed previously reported substrates for all five amino acid transporters.In addition, we propose broader substrate specificity for two of the transporter proteins. The method presented here demonstrates the application of a comprehensive screening platform for the knowledge expansion of the transporter-substrate relationship for native metabolites in S. cerevisiae.